The Role of Learning Motivation on The Influence of School Culture in Improving Students’ Literacy - Edwar, Rizka Cintya; Amin, Muhammad; Khairunnisa, Ayang; Mufti, Digor; Samsinar, Samsinar (Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze the role of learning motivation on the influence of school culture in improving literacy of class XII SMKN 1 Sorong City. This research uses quantitative methods. The population in this study were all students of class XII Accounting and Banking of SMKN 1 Sorong City which amounted to 123 students. The sample size was calculated using the Slovin formula with an error tolerance of 5℅, so a sample size of 95 students was obtained.  Data collection was carried out using a questionnaire, then the data was processed using the SEM PLS program. The results showed that (1) school culture has a positive and significant effect on the literacy of class XII SMKN 1 Sorong City (2) school culture has a positive and significant effect on the learning motivation of class XII SMKN 1 Sorong City, (3) learning motivation has a positive and significant effect on the literacy of class XII SMKN 1 Sorong City (4) class motivation influences positively and significantly on the influence of school culture, on the learning literacy of class XII SMKN 1 Sorong City.